Conceptual model of the perceived quality of city hotels - Marie López Cruz; Yanlis Rodríguez Veiguela; Roberto Carmelo Pons García; Jensy Tanda Díaz (Cooperativismo y Desarrollo, 2022)
Perceived quality is a topic widely addressed in the literature; however, no conceptual model has been established to explain the quality of city hotels, even though they are an essential part of the urban tourism offer, contributing to their positioning as a tourist destination. Identity and urban image become determinants in the value perceived by the client, and therefore influence hotel quality. Based on this, the objective of the research was to propose a conceptual model of perceived quality of city hotels. From this, it was possible to define the relationships between the variables involved in the process. An exploratory and descriptive research was developed, for which a qualitative and quantitative methodology was used. The main results were: the bibliographic review and analysis of the main service quality models, the analysis of the variables most addressed in the literature, the proposal of a model of choice of urban hotels and the proposal of a model of perceived quality of city hotels.